Micellar dendritic structures as drug delivery agents - Böke, Nazlı. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
Among various polymeric systems, amphiphilic block copolymers with stimuli-responsive moities provide significant advantages in drug delivery systems due to their unique self assembly properties which provide interiors that can encapsulate the guest molecules like anti-cancer drugs. The triggered release of these guest molecules can be achieved by external stimuli while minimizing the adverse side effects of the drugs and maximizing the therapeutic effect. In this thesis, various dendron-linear polymer-dendron conjugates are synthesized via Huisgen type “click” reaction using biodegredable polyester dendron and biocompatible PEG. Functionalization of the dendron surface with hydrophobic moiety, which provides pH-sensitivity, increased the tendecy to form micellar structures in water via self-assembly. By changing the length of hydrophilic polymer, type of hydrophobic moiety and generation of the dendron, the optimum micellar structure that can maximize the stability can be achieved. The stability of these micelles at neutral pH is demonstrated by the release rate of a hydrophobic dye. A variety of micelles are phsically encapsulated with an anti-cancer therapeutic agent by co-solvent evaporation method and the drug release is monitored by UV-VIS spectroscopy and LC/MS.
Keywords: Micelles.; Drug targeting.; Drug delivery systems.